Optical Quasiperiodic Oscillations with 550 Day Periodicity in the Reverberation-mapped Broad Line Quasar PG 1411+442 - Xue-Guang Zhang (The Astrophysical Journal)
In this paper, optical quasiperiodic oscillations (QPOs) with 550 day periodicity related to a candidate subparsec binary black hole (BBH) system are reported in the reverberation-mapped broad line quasar PG 1411+442 but with a different line profile of broad H α from that of broad H β in its rms spectrum. First, considering the sine function to describe the 18.8 yr long light curves from the Catalina Sky Survey, All-Sky Automated Survey for Supernovae, and Zwicky Transient Facility, 550 day periodicity can be confirmed with a confidence level higher than 5 σ . Second, the stable 550 day optical QPOs can be reconfirmed with confidence levels higher than 5 σ by the generalized Lomb–Scargle periodogram, the sine-like phase-folded light curves, and the weighted wavelet z -transform technique determined power maps. Third, based on simulated light curves by the continuous autoregressive process, a confidence level higher than 3.5 σ can be confirmed for the optical QPOs not related to intrinsic active galactic nucleus (AGN) variability. Moreover, considering the spatial separation of central two black hole (BH) accreting systems with smaller than expected sizes of broad emission line regions, a central total BH mass higher than 10 ^6 M _⊙ could lead to few effects of supposed BBH systems on estimated virial BH masses. Meanwhile, disk precession is not preferred due to the similar estimated sizes of the optical and near-ultraviolet emission regions, and jet precession can be ruled out due to PG 1411+442 being a radio-quiet quasar. The results strongly indicate it would be practicable, by applying very different line profiles of broad Balmer emission lines, to detect candidate BBH systems in normal broad line AGN in the near future.